1982
DOI: 10.1111/j.1399-3054.1982.tb00271.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of NaCl salinity and water stress with polyethylene glycol on nitrogen fixation, stomatal response and transpiration of Medicago sativa, Trifolium repens and Trifolium brachycalycinum (subclover)

Abstract: 1982. The effect of NaCl salinity and water stress with polyethylene glycol on nitrogen fixation, stomatal response and transpiration of Medicago sativa, Trifolium repens and Trifolium brachycalycinum (subclover). -Physio). Plant. 54: 361-366.The objective of this study was to investigate the behaviour of different leg,umes against salinity and water stress, thus trying to discover simultaneous adaptations to both stresses. The nitrogen fixation, transpiration, predawn leaf water potential, and stomatal respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 18 publications
4
12
0
Order By: Relevance
“…1). These results agreed with those of Plaut and Federman (1985) and with Sanchez-Diaz et al (1982) who found that P E G decreased leaf conductance and carbon dioxide fixation rates in tomato and legumes more severely than did NaC1. Reduction in stomatal conductance due to NaC1 was found to be associated with accumulation of sodium in the leaves (Walker et al, 1983).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…1). These results agreed with those of Plaut and Federman (1985) and with Sanchez-Diaz et al (1982) who found that P E G decreased leaf conductance and carbon dioxide fixation rates in tomato and legumes more severely than did NaC1. Reduction in stomatal conductance due to NaC1 was found to be associated with accumulation of sodium in the leaves (Walker et al, 1983).…”
Section: Discussionsupporting
confidence: 83%
“…Polyethylene glycol (PEG) compounds have been widely used to simulate water stress effects in plants. Several investigators have examined the effects of NaCI and PEG on growth and ion absorption in bean, maize, sorghum (Kawasaki et al, 1983a), barley (Kawasaki et al, 1983b), legumes (Sanchez-Diaz et al, 1982), and tomato * Florida Agricultural Experiment Station Journal Series No. 9941.…”
Section: Introductionmentioning
confidence: 99%
“…High salt concentrations cause osmotic stress after short-term exposure or ion toxicity after long-term exposure in plants (Munns and Tester, 2008;Sanchez-Diaz et al, 1982;Zeng, 2005). Sodium chloride (NaCl) is the salt of main concern due to its high solubility (Munns and Tester, 2008) with 40 mM considered problematic for agriculture (Munns and Tester, 2008).…”
Section: Salinitymentioning
confidence: 99%
“…Along with the algal concentration going up, 24-ethyl sterol (sitosterol and stigmasterol) content in plants increased more than that of 24-methyl sterol (campesterol), moreover, the ratio between campesterol and stigmasterol plus sitosterol decreased from 18.5% to 16.2%, which showed that M. aeruginosa affected the second alkyl side chain at C-24 position of plant sterol in the biosynthesis process of sterol in vivo P. maackianus [24][25][26][27] . The first deteriorative change during stress injury is an alteration in the structure and function of cell membranes, which results in an impaired ability to retain solutes [28] . The structure and function of cell membranes would be influenced by sterols [26] .…”
Section: Discussionmentioning
confidence: 99%